Intestinal Epithelial Cell-Derived CD83 Contributes to Regulatory T-Cell Generation and Inhibition of Food Allergy - Yong Yu; Qiao-Ruo Jin; Yang Mi; Jiang-Qi Liu; Zhi-Qiang Liu; Shuai Wang; Zhi-Gang Liu; Ping-Chang Yang; Peng-Yuan Zheng (Karger Publishers, 2021)
The mechanism of generation of antigen-specific regulatory T cells (Treg) is not fully understood yet. This study aimed to investigate the role of intestinal epithelial cell (IEC)-derived CD83 in the Treg generation in the intestine. In this study, the role of CD83 in the generation of Tregs was assessed in a cell-culture model and a food allergy (FA) mouse model. We found that mouse IECs expressed CD83; its levels were markedly lower in sensitized mice. Mice with CD83-deficient IECs failed to induce Tregs in the intestine. CD83 promoted the transforming growth factor-β-inducible early gene 1 (TIEG1) expression in CD4+ T cells. Toll-like receptor 4 (TLR4)/myeloid differentiation protein-2 (MD-2) complex mediated the effects of CD83 on the expression of TIEG1. Activation of the CD83/TLR4/MD-2/TIEG1 promoted the Treg generation. Concomitant administration of CD83 and specific antigens, but not either one alone, efficiently inhibited experimental FA via inducing the Treg generation in the intestine. In Conclusion, IEC expresses CD83 that is low in sensitized mice. Concomitant administration of CD83 and specific antigens efficiently inhibits FA in a murine model via inducing Tregs in the intestine. The data suggest that CD83 has translation potential in the treatment of FA.